Demystifying the magnetic drag of the Indo-pacific region - Puri, Vivek (IIPA Digest)
The tides and currents of the Indo-Pacific have alerted the major economic and political powerhouses of the world about the relevance of safety and security in the region in every sense. Almost every nation is now pondering and diving deep into the strategic depths to frame the geoeconomics policies and geostrategic plan of actions that suit their nation vis-à-vis the Indo-Pacific region. This article forms an opinion about the relevance of the Indo-Pacific, the geopolitical shifting of gears in the region, and further attempts to understand the new maritime challenges, the strategic policies of various nations, and how India s strategic plan of action can act as the best way forward in the Indo-Pacific region.- Reproduced
Keywords: Indo-Pacific, Geoeconomics policies